THE ROLE OF COLLABORATION BETWEEN FORENSIC SCIENCE ORGANIZATIONS IN THE CONTEXT OF EURASIAN INTEGRATION - A. Usov; N. Govorina (Теория и практика судебной экспертизы, 2015)
Contemporary development of forensic science depends on collaboration between forensic science organizations in member states of the Eurasian Economic Community (EurAsEC). The Coordination and Methodology Commission on Forensic Science of the Council of Ministers of Justice of EurAsEC member states completed its work in 2014. The paper analyzes its key outcomes.